Peran Pelayanan Penggembalaan Terhadap Pertumbuhan Iman Jemaat - Kamau, Dolof Martin; Sanger, Christina (Sekolah Tinggi Teologi Pelita Hati, 2024)
Faith growth is a continuing process after every believer accepts Jesus as Lord and Savior personally. In its dynamics, the growth of faith is heavily influenced by internal and external factors, where in this study the focus is narrowed to external factors in the growth of faith, namely the role of shepherding. The research method used is the literature study method, in which it is found that the teaching, advice and examples of pastors in shepherding play an important role in the growth of the congregation's faith.